Vaiyāsakanyāyamālā : Vedāntādhikaraṇanyāyamālā - Bhāratītīrtha (Ānandāśramasaṃskrtagranthāvaliḥ, 1980)
Verse commentary, with autocommentary, on Bādarāyaṇa's Brahmasūtra, basic work of the Vedanta school in Hindu philosophy, from the Advaita point of view.